Designing and Validating a Basketball Learning and Performance Assessment Instrument (BALPAI) - Ibáñez, Sergio J.; Martinez-Fernández, Sergio; Gonzalez-Espinosa, Sergio; García-Rubio, Javier; Feu, Sebastián (Frontiers in Psychology, 2019)
Introduction: The assessment of learning in basketball in the PE class, and in training sessions of young players, requires valid, reliable, and trustworthy tools. The purpose of this research was to design and validate the Basketball Learning and Performance Assessment Instrument (BALPAI) that assesses at the same time decision making, technical execution and efficacy. Method: A pilot study was performed following this procedure. A group of 13 experts participated in the assessment of the 33 elements (66 items) included in the BALPAI. Aiken's V formula was used to analyse content validity, and internal consistency was calculated using Cronbach's α. Interobserver reliability was calculated with the Multirater κfree. Results: The BALPAI has very high internal consistency (.969), and Interobserver reliability was almost perfect (>.84 in all items). Conclusion: The BALPAI proved to be a valid tool, with high internal consistency and reliability, that makes it possible to perform a complete assessment of basketball both in PE classes, and in sports training. Next step will be a general application at scholar and training level to check the learning performance.